High‐throughput environmental sequencing reveals high diversity of litter and moss associated protist communities along a gradient of drainage and tree productivity. (12th March 2018) - Heger, Thierry J.; Giesbrecht, Ian J. W.; Gustavsen, Julia; del Campo, Javier; Kellogg, Colleen T. E.; Hoffman, Kira M.; Lertzman, Ken; Mohn, William W.; Keeling, Patrick J.
Summary: Although previous studies, mostly based on microscopy analyses of a few groups of protists, have suggested that protists are abundant and diverse in litter and moss habitats, the overall diversity of moss and litter associated protists remains elusive. Here, high‐throughput environmental sequencing was used to characterize the diversity and community structure of litter‐ and moss‐associated protists along a gradient of soil drainage and forest primary productivity in a temperate rainforest in British Columbia. We identified 3262 distinct protist OTUs from 36 sites. Protists were strongly structured along the landscape gradient, with a significant increase in alpha diversity from the blanket bog ecosystem to the zonal forest ecosystem. Among all investigated environmental variables, calcium content was the most strongly associated with the community composition of protists, but substrate composition, plant cover and other edaphic factors were also significantly correlated with these communities. Furthermore, a detailed phylogenetic analysis of unicellular opisthokonts identified OTUs covering most lineages, including novel OTUs branching with Discicristoidea, the sister group of Fungi, and with Filasterea, one of the closest unicellular relatives to animals. Altogether, this study provides unprecedented insight into the community composition of moss‐ and litter‐associated protists.